Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

L'héritage de l'esclavage : éléments pour une autre approche de la condition de femme - Davis, Angela (Femmes, race et classe, 2007)
Première publication: 1983
Keywords: afro-féminisme; amériques; approches et analyses; classe sociale; cours; fem1000; féminismes noirs; histoire et politique; inégalités; militance; premier cycle; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Le viol, le racisme et le mythe du violeur noir - Davis, Angela (Femmes, race et classe, 2007)
Première publication 1981
Keywords: afro-féminisme; amériques; approches et analyses; cours; fem1000; féminismes noirs; inégalités; militance; premier cycle; racisme; régions géographiques; stéréotypes; systèmes d'oppressions; thématiques; travail; violences; états-unis

Cartographies des marges : intersectionnalité, politique de l'identité et violences contre les femmes de couleur - Crenshaw, Kimberlé W. (Cahiers du Genre, 2005)
Les discours féministes et antiracistes contemporains n’ont pas su repérer les points d’intersection du racisme et du patriarcat. Face à ces difficultés, cet article propose une approche originale : l’intersectionnalité. La première partie traite de l’intersectionnalité structurelle — de la manière dont le positionnement des femmes de couleur, à l’intersection de la race et du genre, rend leur expérience concrète de la violence conjugale, du viol et des mesures pour y remédier qualitativement différente de celle des femmes blanches. La seconde partie porte sur l’intersectionnalité politique : notamment la marginalisation de la question de la violence contre les femmes de couleur induite par les politiques féministes et antiracistes. Enfin, l’article conclut par l’examen des conséquences de l’approche intersectionnelle dans le champ plus large de la politique de l’identité contemporaine. [*]
https://www-cairn-info.proxy.bibliotheques.uqam.ca/revue-cahiers-du-genre-2005-2-page-51.htm
Keywords: 1900-1999; afro-féminisme; amériques; approches et analyses; com5170; cours; cycles supérieurs; fem1000; fem3300; fem7000; féminismes noirs; har4600; har4610; incontournable; intersectionnalité; lit2815; lit3220; lit3495; patriarcat; phi4336; pol4022; pol4102; pol4105; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; états-unis

Black sexual politics: African Americans, gender, and the new racism - Hill Collins, Patricia (Routledge, 2005)
To a large extent, scholarship on black politics often focuses primarily on institutions, rule of law, processes, political actors, and citizens but with very little attention to issues of gender and sexuality. In contrast, the principal aim of this book is to explore what the author sees as the inextricable links between racism and gender. The basic thesis of this well-written, important, and provocative book is that the fight against racism, especially the “new racism,” can never be won without first challenging sexism, which simultaneously oppresses African-American men and women.
Section: ix, 374 p. ; 23 cm
Keywords: afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; féminismes noirs; intersectionnalité; premier cycle; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; théorie critique de la race; violences; états-unis

Domestic violence at the intersections of race, class, and gender: challenges and contributions to understanding violence against marginalized women in diverse communities - Sokoloff, Natalie J; Dupont, Ida (Violence against women, 2005)
This article provides a comprehensive review of the emerging domestic violence literature using a race, class, gender, sexual orientation intersectional analysis and structural framework fostered by women of color and their allies to understand the experiences and contexts of domestic violence for marginalized women in U.S. society. The first half of the article lays out a series of challenges that an intersectional analysis grounded in a structural framework provides for understanding the role of culture in domestic violence. The second half of the article points to major contributions of such an approach to feminist methods and practices in working with battered women on the margins of society.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; care; corps; cours; criminologie; discipline; féminisme afroaméricain; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; violences; états-unis